(untitled) (Alberta Journal of Educational Research, 2003)
This article discusses the implications of the dichotomy between Native North American oral traditions and Western literacy with special attention to storytelling and its implications for the definition of a school curriculum that would be inclusive of Native perspectives. Specifically, the author refers to the work of Eliade (1960, 1963) in examining the nature of myth as a particular form of narrative while addressing some critiques to his analysis of Native cosmology. This discussion enables the author to construct a critique of Egan’s (1986) theoretical model of the use of storytelling in education from a First Nations perspective.